Organisasi bukan kerajaan (NGO) berkebajikan melayu Islam di Malaysia: dorongan dan amalan keusahawanan sosial terhadap program pembangunan komuniti - Marwan Ismail (2017)
Social entrepreneurship has attracted the attention among policy makers and also non- governmental organizations in accomodating community developmental issues in the 21st century. Social entrepreneurship is seen to be able to assist NGOs in organizing community development programmes in Malaysia independently without having to depend on financial support from external funds. There is shortage of research on the patterns of social entrepreneurship practices and factors that influence the involvement of volunteers in Non-Government Organization-Berkebajikan Melayu Islam (NGO- BMI). Therefore, this study attempted to investigate matters pertaining challenges in managing NGO-BMI that involved in the community empowerment programmes in Malaysia. This study adopted qualitative research methodology by conducting interviews with 20 informants from the top management and also subordinates from 11 NGO-BMls. This study also utilized quantitative data from a survey collected from 219 NGO staff and volunteers to support the research. This research identified four main domains namely social business, identifying opportunity, social innovation and social values to be examined besides analysing variables such as religious vaues, educational background and leadership styles in those NGO-BMI. The study found that social entrepreneurship approach has yet to be adopted as the main strategy in generating income for NGO-BMI in Malaysia. This study also found that religious factors, the practice of democratic leadership style and syura (consultative or participative) leadership style influenced the volunteers' involvement in NGO-BMI. Although educational background was not considered as a primary factor that influenced the volunteers' involvement in NGO-BMI, this factor significantly contributed to the development of volunteers' self-esteem and helped them to become more innovative when performing their tasks in NGO-BMI. The findings of this research revealed that internal and external factors such as leadership, finance, facilities, community empowerment programmes managenment, attitudes of the targeted groups and also partnership agencies were the main challenges that need to be dealt in managing NGO- BMI. Therefore, social entrepreneurship approach, factors that motivate the volunteers' involvement and challenges in managing NGO-BMI should seriously be given consideration by the stakeholders in planning and implementing community empowerment programmes in Malaysia.